Assessing health-related quality of life of patients with colorectal cancer using EQ-5D-5L: a cross-sectional study in Heilongjiang of China. Issue 12 (6th December 2018) - Huang, Weidong; Yang, Jinjin; Liu, Yang; Liu, Chaojie; Zhang, Xin; Fu, Wenqi; Shi, Limei; Liu, Guoxiang
Abstract : Aim: This study aimed to assess the health-related quality of life (HRQoL) of patients with colorectal cancer (CRC) and its determinants. Methods: A cross-sectional questionnaire survey was conducted on 300 newly diagnosed patients with CRC in China's Heilongjiang province, measuring HRQoL using the EuroQol five-dimension five-level (EQ-5D-5L). Kruskal-Wallis analyses were performed to identify the independent variables associated with the EQ-5D-5L utility scores. Predictors of the utility scores were confirmed using a Tobit regression model. Results: The respondents had a mean EQ-5D-5L utility score of 0.617 (SD=0.371) and a median of 0.740 (range: −0.348 to 1.000). Pain/discomfort and anxiety/depression were major concerns of the respondents, with a prevalence of over 60% (all levels inclusive). The Kruskal-Wallis analyses found lower utility scores in those who were not married, worked as a farmer, enrolled with the new rural cooperative medical scheme and had lower household income (p<0.05). Those who were at a later stage of CRC, underwent surgical only therapy and had a stoma also had lower EQ-5D-5L scores than others (p<0.05). The Tobit regression model confirmed these predictors, except for occupation and marital status. Conclusion: Patients with CRC have poor HRQoL, with pain/discomfort and depression/anxiety as the most frequently reported problems. The poor HRQoL is associated with the seriousness of the disease condition, as well as the low socioeconomic status of the patients.